Completed local binary pattern based speech anti-spoofing - Jian XU; Zhihua JIAN; Jiaqi YU; Yifan JIN; Lin YOU; Yunlu WANG (Dianxin kexue)
In view of the fact that the disguised speech detection algorithm based on local binary pattern (LBP) is not effective in detecting the spoofing attack from voice conversion, an anti-spoofing method based on completed local binary pattern (CLBP) was proposed.In this method, the spectrogram of speech signals is generated by the variable Q transformation (VQT) and used to train the true/spoofed speech classifier, so as to perform the detection of disguised speech.The experimental results demonstrate that the proposed anti-spoofing method based on the CLBP in the detection of voice conversion deception is better than the LBP-based algorithm, and when the parameter γ in VQT is set to 50, the detection system based on CLBP and SVM-RBF has the best performance for anti-spoofing the disguise speech.